New lichen biota records from Santuario Histórico de Machu Picchu, Peru - Nuñez-Zapata, Jano (2015)
While high species diversity of lichen - lichenized fungi - is reported especially in the tropics, the studies on these organisms are still scarce in Peru. Using conventional methodology and current literature on the description of genera and species, we reported macro-lichens collected from Historic Sanctuary of Machu Picchu (Cusco, Peru). Sixty seven species of macro-lichens are reported to SHMP, nine new records to Peru are documented. Parmeliaceae, Physciaceae and Lobariaceae are the families with major number of species.